2014
DOI: 10.1210/jc.2013-3584
|View full text |Cite
|
Sign up to set email alerts
|

An Independent Study of a Gene Expression Classifier (Afirma) in the Evaluation of Cytologically Indeterminate Thyroid Nodules

Abstract: The Afirma GEC demonstrates a lower than expected rate of benign reports in follicular or Hürthle cell neoplasm and a lower than anticipated malignancy rate within GEC-suspicious nodules. These data suggest that the positive predictive value of the GEC is lower than previously reported and call into question the performance of the test when applied in the context of specialized academic cytopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
212
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 202 publications
(227 citation statements)
references
References 20 publications
15
212
0
Order By: Relevance
“…In an independent study, the sensitivity and specificity rates achieved by Afirma were reported to be 83% and 36%, respectively, and were the best rates of the case scenarios. 44 If lower sensitivity and specificity than anticipated are confirmed, then both predictive values would be negatively affected.…”
Section: Transcriptional Levelmentioning
confidence: 94%
“…In an independent study, the sensitivity and specificity rates achieved by Afirma were reported to be 83% and 36%, respectively, and were the best rates of the case scenarios. 44 If lower sensitivity and specificity than anticipated are confirmed, then both predictive values would be negatively affected.…”
Section: Transcriptional Levelmentioning
confidence: 94%
“…The diagnostic performance of the GEC test was subsequently reported in 4 respective studies from the USA [29-32]. In each of these studies, treating physicians were aware of the GEC result at the time of surgical decision-making and not all patients who underwent a GEC test had gold-standard histopathological confirmation of the diagnosis; furthermore, there was no reported blinding of the histopathologists who ascertained the gold-standard diagnosis (when performed) [29-32].…”
Section: Should a Microarray Gec Test Be Routinely Used On An Indetermentioning
confidence: 99%
“…In each of these studies, treating physicians were aware of the GEC result at the time of surgical decision-making and not all patients who underwent a GEC test had gold-standard histopathological confirmation of the diagnosis; furthermore, there was no reported blinding of the histopathologists who ascertained the gold-standard diagnosis (when performed) [29-32]. McIver et al [29] reported in a prospective register study that patients at the Mayo Clinic (Rochester and Jacksonville sites) were offered the GEC test if the FNA was performed on site and the cytology was reported as SFN, suspicious for Hürthle cell neoplasm, or AUS/FLUS; approximately 83% (30/36) of the specimens included in the final analysis were SFN or suspicious for Hürthle cell neoplasm. In this study, criteria for offering GEC testing to patients with indeterminate cytology thyroid nodules included willingness of the patient to defer surgery, lack of compressive symptoms, and absence of higher-risk features (including head and neck radiation history, family history of thyroid cancer, prior history of thyroid cancer, or worrisome imaging characteristics) [29].…”
Section: Should a Microarray Gec Test Be Routinely Used On An Indetermentioning
confidence: 99%
“…The role of the GEC in cytologically indeterminate nodules that are SFM is less clear, and the test is not reflexively performed. Two recent reports with small sample sizes have independently evaluated GEC use in single-center studies, and the results emphasize the importance of cancer prevalence in interpretation of NPV and PPV (38,41). Harrell et al evaluated 35 patients with indeterminate cytology, histology, and GEC results, and had an observed cancer rate of 51%.…”
Section: Gecmentioning
confidence: 99%